Multi-Domain Model for Electric Traction Drives Using Bond Graphs - Silva, Luis Ignacio (2011)
In this work the Multi-Domain model of an electric vehicle is developed. The electric domain model consists on the traction drive and allows including faults associated with stator winding. The thermal model is based on a spatial discretization. It receives the power dissipated in the electric domain, it interacts with the environment and provides the temperature distribution in the induction motor. The mechanical model is a half vehicle model. Given that all models are obtained using the same approach (Bond Graph) their integration becomes straightforward. This complete model allows simulating the whole system dynamics and the analysis of electrical/mechanical/thermal interaction. First, experimental results are aimed to validate the proposed model. Then, simulation results illustrate the interaction between the different domains and highlight the capability of including faults.